Problem sztuki naskalnej w Polsce - Pankiewicz, Marek (Folia Praehistorica Posnaniensia, 2022)
It is assumed that occurrence of Palaeolithic cave art in Central and Eastern Europe is not typical for this part of the continent, as it is difficult to consider its few examples as a result of solely poor preservation. Looking into this issue from the perspective of region of modern Poland, several questions arise: Why is it registered on so few sites, and is it truly an atypical phenomenon for the region? In problem discussion, there are three key elements: research interest, state of preservation, and competences needed for making a discovery. These elements, covered in following paper, explicitly suggest that in terms of Polish cave sites, we do not possess enough information to conclude which type of occurrence we are dealing with.